Optimizing the acid resistance of concrete with granulated blast-furnace slag - Luca-Alexander Kempf; Rolf Breitenbücher; Christian Gerten; Andreas Ehrenberg (Acta Polytechnica CTU Proceedings, 2022)
Concrete structures exposed to high levels of chemical attacks are assigned to exposure class XA3, which recommends separate concrete protection or a special expert solution to ensure durability. Due to the partial substitution of Portland cement by blast-furnace slag, an increased resistance to acid attacks could be achieved within the framework of a research project. The technical and ecological advantages of cements containing granulated blast-furnace slag were exploited through chemical, granulometric and concrete technological optimizations. Despite extensive parameters, a statistical test design (DoE) was able to limit the experimental effort, thus defining principles for the conception of binder systems with increased chemical resistance.Mortar prisms indicated that the use of (ultrafine) blast-furnace slags (up to 13,000 cm2/g according to Blaine) with a broad particle size distribution can have a positive effect both on the capillary/gel pore ratio and on the calcium hydroxide content in the cement stone. Furthermore, the chemical composition of the blast-furnace slag as well as the water-binder ratio are decisive influencing factors for the acid-resistance, which was confirmed in accelerated acid resistance tests on concretes (pH-stat method). After 13 weeks of storing concrete specimens in sulfuric acid (H2SO4, pH 3.5), reduced damage depths and lower weight losses were observed compared to conventional binder compositions. The results serve as a basis for the development of highly acid-resistant concretes using blast-furnace slag-containing binder systems. Currently, the acid resistance of those concretes is being investigated in a long-term study by outsourcing representative test specimens into the Emscher sewer.